DEVELOPING PURCHASE INTENTION OF EIGER PRODUCTS IN KUDUS - Marka, Mira Meilia; Whenda Adyakarsa, Ryan; Subono, Agung (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to analyze the influence of e-wom and social media marketing on purchase intention for Eiger products through brand image among Muria Kudus University students. The approach used is a quantitative approach. The sample used in this research was 120 respondents selected using proportional sampling technique. The data collection technique uses a questionnaire method. The data analysis technique uses AMOS structural equation model analysis. The results obtained are: : 1) e-wom and social media maketing have a positive and significant effect on brand image, 2) e-wom has no effect on purchase intention, 3) social media marketing has a positive and significant effect on purchase intention, 4) brand image has a positive and significant effect on purchase intention, 5) e-wom has a positive and significant effect on purchase intention through brand image, and 6) social media marketing has a positive and significant effect on purchase intention through brand imge.